Usher syndrome: Clinical features, diagnostic options, and therapeutic prospects - Seeliger, M; Fischer, M; Pfister, M (2009)
Usher syndrome denotes a clinically and genetically heterogeneous combination of retinitis pigmentosa and sensorineural deafness. The division into subtypes I, II, and III is based on the degree of hearing loss: Type I is characterized by deafness from birth together with ataxia and retarded motor development, type II by a stationary deafness of a moderate degree, and type III by a progressive deafness with adult onset. In Germany, Usher syndrome currently bears particular relevance because in January 2009 a new compulsory screening of auditory function in newborn infants was introduced. Consequently, it can be expected that a higher number of patients with Usher syndrome will be identified in early childhood and referred to ophthalmologists. The focus of this work is to introduce the typical clinical picture of Usher syndrome, summarize diagnostic options, and give an overview of therapeutic strategies. © 2009 Springer Medizin Verlag.